Does the use of renewable energy increase carbon productivity? ——An empirical analysis based on data from 30 provinces in China. (10th September 2022) - Meng, Siqi; Sun, Renjin; Guo, Feng
Abstract: Renewable energy consumption has a strong driving force for promoting energy conservation and emission reduction, and is a new way to achieve clean and low-carbon development. Based on this, this paper uses the data of renewable energy consumption, carbon productivity, GDP, population, energy efficiency and technological innovation of 30 provinces in China from 2011 to 2020, and empirically analyzes the impact of renewable energy consumption on carbon productivity in 30 provinces in China, using STIRPAT model, comprehensively considers spatial horizontally and temporal vertically dimension. The empirical results show that: (1) China's carbon productivity shows a significant spatial spillover effect, its impact can spill over to adjacent areas within 1000 km; (2) China's renewable energy power consumption plays a significant role in promoting the improvement of carbon productivity. (3) Renewable energy consumption in the western region plays the most important role in driving carbon productivity. Finally, according to the temporal and spatial relationship between renewable energy consumption and carbon productivity in different regions, we provide specific regional policy suggestions. Highlights: The STIRPAT model is employed to explore temporal and spatial impact, while it considers sub regions. Spatialy, the impact can spill over to adjacent areas within 1000km. Temporally, the impact fluctuates and rises. The positive role of renewable energy consumption is found in China's western region.